Pemanfaatan Hand Tracking untuk Membuat Program Virtual Painter sebagai Alternatif Menggambar Digital - Oktaviyanti, Dwi; Nugroho, Anan; Suni, Alfa Faridh (PETIR, 2022)
Technology will always develop every day. One of the widely used concepts is the Human Machine Interface. An example is the stylus which allows you to draw on a tablet, laptop, or other compatible device. The results of the images that are directly connected to the computer make many people like this use. However, not many people still use paper for drawing because the stylus is quite expensive and requires a device that is compatible with the stylus. The purpose of this journal is to create a program that allows users to draw digitally without the need for touch screen devices or other tools, just by moving their hands in front of the camera to draw and the results can be directly seen on the computer. The method used is the concept of hand tracking to track the movement of the fingers used for drawing. The results obtained are the program detects 21 keyponits hand landmark users using a 30 fps webcam. These keypoints are analyzed to further determine the current mode (select or draw). The resulting image can be directly seen in the input frame. Program accuracy can reach 100% with medium to high light intensity and with a distance of 50-100 cm.